2020
DOI: 10.1002/gcc.22906
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prognostication of uterine smooth muscle neoplasms: FromCGHarray toCINSARCsignature and beyond

Abstract: Uterine leiomyoma and leiomyosarcoma are located at the ends of the spectrum of smooth muscle lesions. Leiomyosarcoma belongs to the complex genomic sarcomas characterized by complex karyotypes. In contrast, leiomyoma, has a low level of chromosomal complexity. The analysis of genomic profiles of uterine smooth muscle tumors shows that genomic complexity, which is an expression of chromosomal instability, correlates with the metastatic potential and malignity of tumors: the more genetically complex a smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…In leiomyosarcomas, genetic mutation burden exhibited higher copy number variations, single nucleotide variants, small insertions/deletions, and gene fusions compared with uterine fibroids. Comparative genomic hybridization (CGH) array analysis reveals a chromosomal and genomic complexity starting from uterine fibroids, with few chromosomal alterations, to uterine leiomyosarcoma, which harbors many intrachromosomal damages, and chromothripsis as evidence of their genomic complexity ( 116 , 424 , 425 ). In addition, a differential transcriptomic profile was observed for uterine leiomyosarcomas ( 423 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In leiomyosarcomas, genetic mutation burden exhibited higher copy number variations, single nucleotide variants, small insertions/deletions, and gene fusions compared with uterine fibroids. Comparative genomic hybridization (CGH) array analysis reveals a chromosomal and genomic complexity starting from uterine fibroids, with few chromosomal alterations, to uterine leiomyosarcoma, which harbors many intrachromosomal damages, and chromothripsis as evidence of their genomic complexity ( 116 , 424 , 425 ). In addition, a differential transcriptomic profile was observed for uterine leiomyosarcomas ( 423 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition to immunochemistry, more sophisticated methods can be applied. In uterine tumors with uncertain malignant potential, the assessment of genomic index by comparative genomic hybridization array, that is, counting the genomic complexity of a tumor, allows leiomyosarcomas to be distinguished from benign tumors such as leiomyomas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated features of UL karyotype evolution [ 37 , 40 , 45 , 66 , 67 , 68 , 69 ]. However, benign UL is more cytogenetically stable compared to its malignant counterpart—leiomyosarcoma [ 41 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%